Effect of negative half-wave alternating current on stress corrosion cracking behavior and mechanism of X80 pipeline steel in near-neutral solution. (15th November 2017) - Wan, Hongxia; Song, Dongdong; Liu, Zhiyong; Du, Cuiwei; Zeng, Zhongping; Wang, Zhigao; Ding, De; Li, Xiaogang
Highlights: The AC was divided into negative half wave to study the effect on the SCC behavior of X80 steel. Reason for different SCC susceptibility under various negative half wave AC density was studied. The SCC mechanism was investigated in near-neutral solution under the negative half wave AC. Abstract: The influence of various negative half-wave alternating current (AC) densities on the stress corrosion cracking (SCC) behavior and mechanism of X80 pipeline steel (widely used in West-East natural gas transmission) was investigated in typical NS4 near-neutral solution (used to simulate the electrolyte trapped under a disbonded coating) by data acquisition technique, electrochemical method, immersion tests, slow strain rate tensile tests, and surface analysis techniques. It was found that the negative half-wave AC could accelerate corrosion of the steel for the potential decreasing, current density increasing and generating the local anodic dissolution such as nucleated pits. The SCC susceptibility of X80 steel was relatively high for disturbing the local double-charge layer structure at 5 A·m −2 current density. Besides, the negative half-wave AC could promote cathodic hydrogen evolution reaction, the SCC susceptibility was low for hydrogen-induced plasticity at 10 and 20 A·m −2 and the SCC mechanism was collectively controlled by anodic dissolution (AD) and hydrogen embrittlement, but it was elevated for the hydrogen-induced local anodic dissolution and hydrogen-induced embrittlement above 30 A·m −2 and the SCC mechanism was hydrogen embrittlement.